The Effect Of Brand Value, Brand Awareness, Brand Loyality On Brand Equity In Sharia Banking Industry - endang endang; rr Lulus prapti NSS; Teguh Ariefiantoro (JURNAL STUDI MANAJEMEN ORGANISASI, 2021)
Brand equity is one of the core aspects of marketing, all marketing strategies are basically the goal of building a solid brand. Brands have solid equity to succeed in gaining loyal customer marketing and financial benefits. When before deciding to become a customer or client, of course, consumers are inflated by many things that motivate them. Therefore it is very meaningful to analyze the key factors that motivate the use of brand equity and customer service at that time to look for correlations and obtain suitable conclusions. The object that is being studied is the customer of Islamic banking.. The purpose of this research is to identify the impact of brand value, Brand Awareness, Brand Loyality on Brand Equity at Bank Muamalat in Semarang. The research method used in this research is through a survey. Information is analyzed quantitatively and uses a causal research design. The method of taking illustrations used in this research is to use Non-Probability Sampling with purposive sampling method. All of the illustrative information obtained by distributing questionnaires is 100 respondents and will be processed using the SPSS 24 software feature